2019
DOI: 10.1063/1.5097779
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of physical aging and thixotropy in aqueous dispersion of Carbopol

Abstract: In this work, we investigate signatures of physical aging in an aqueous dispersion of Carbopol that shows yield stress and weak enhancement in elastic modulus as a function of time. We observe that the creep curves, as well as strain recovery, show a significant dependence on waiting time elapsed since shear melting.The corrected strain, which is the strain in excess of the recovered strain, has been observed to show time -waiting time superposition in the effective time domain, wherein time is normalized by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 82 publications
7
37
3
Order By: Relevance
“…The constituting elements within the system had mobility, and this in turn led to them exploring the phase space, altering its' configuration over time to lower their free energy. The need to minimize free energy (physical ageing) was what [24] believed to be the cause for the drop in viscosity observed; the present study does not agree with this hypothesis as it needs further validation.…”
Section: Introductioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The constituting elements within the system had mobility, and this in turn led to them exploring the phase space, altering its' configuration over time to lower their free energy. The need to minimize free energy (physical ageing) was what [24] believed to be the cause for the drop in viscosity observed; the present study does not agree with this hypothesis as it needs further validation.…”
Section: Introductioncontrasting
confidence: 73%
“…There have been studies to understand the ageing phenomena in Carbopol systems, where it has been shown that the viscosity, storage (G′) and loss (G″) moduli changed over time for water-based gel systems [24,25]. One hypothesis advanced by Agarwal et al [24], was that the changes in viscosity were due to physical ageing. It was suggested that the gel systems were in a high free energy state upon initial formulation.…”
Section: Introductionmentioning
confidence: 99%
“…5). The ability to measure the effect of time can also be useful to investigate the complex coupling between viscoplastic deformation, aging, and rejuvenation (Agarwal and Joshi 2019;Coussot 2018;Joshi and Petekidis 2018). Moreover, the methodology used appears competitive compared to some others (Kashani et al 2015) for its simplicity.…”
Section: Conclusive Remarksmentioning
confidence: 99%
“…Within dynamic experiments, the sample is exposed to a forced sinusoidal oscillation and the transmitted stress is measured. Both types of testing are used for the evaluation of structure and physical aging of aqueous dispersions of carbomer gels (17,(39)(40)(41). The results of the oscillatory rheological characterization of the investigated hydrogels are presented in Table V and Figure 3.…”
Section: Table III Apparent Viscositiesmentioning
confidence: 99%
“…The application properties of hydrogels largely depend on formulation factors that may affect the rheological characteristics of the system, including physico-chemical properties and concentrations of a gelling agent and an active substance. The most often used gelling agents in topical hydrogels are carbomers, which represent high-molecular homo-polymers of acrylic acid crosslinked by polyethers (16,17). Carbomer hydrogels are viscoelastic systems obtained by the dispersion of polymer powders in water and subsequent neutralization with a suitable base, so that the dry particles swell, and polymer chains undergo extensive expansion (15).…”
Section: Introductionmentioning
confidence: 99%